Terrain and climate change impact on WUE of durum wheat in a semi-arid hilly catchment - Ferrara R.M.; Introna M.; Martinelli N.; Rana G. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
Until now, any simulation model has investigated in detail the terrain effects (slope, elevation and azimuth effects) on the crop growth in function of climate changes. The focus of this paper is to relate predicted yields of wheat crops to topographic characteristics, analysing the vulnerability in future scenarios with respect to crop cultivated in plane in a semi-arid region in South Italy. The presented simulation is based on the model STAMINA, which is the result of a European project (EU-QLK-5- CT-2002-01313) where a risk assessment for arable agriculture in hilly landscape has been done in detail in the final report of the project. This complex cropping system model, integrating spatial information, simulates agro-meteorology, hydrology, crop development and photosynthesis in hilly terrain, deriving, among others variables, Agro-Ecological Indicators (AEI) for aiding decision makers to improve sustainable farming at the catchment scale. Among the AEI indicators obtainable by STAMINA model, the WUE, defined by the ratio of yield and cumulative actual evapotranspiration, has been analysed to show how the spatial heterogeneity of the landscape affected its distribution in time and space. Moreover, a study on how management practices could mitigate negative impacts of climate change and topography is done.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)